Lipid and lipoprotein measurements and the risk of ischemic vascular events: Framingham Study - Pikula, Aleksandra (Neurology, 2015)
OBJECTIVES: To examine the relationship between plasma lipid measurements and incident ischemic vascular events (ischemic stroke [IS], and as a positive control, myocardial infarction [MI]) in a community cohort. METHODS: In 6,276 stroke-free Framingham participants (aged 64 ± 10 years, 56% female), we related plasma lipid levels (total cholesterol [TC], high-density lipoprotein cholesterol [HDL-C], and TC/HDL-C ratio) measured at the original cohort 15th (1977–1979) and 20th examination cycles (1986–1990) and (TC, HDL-C, TC/HDL-C ratio, triglycerides [TG], and low-density lipoprotein cholesterol [LDL-C]) measured at the offspring fourth examination (1995–1998), to 10-year risk of incident IS and MI. Utilizing genome-wide genotyping in the same subjects, we used mendelian randomization methods to assess whether observed associations were incidental or causal. RESULTS: During a mean follow-up of 9 years, 301 participants experienced incident IS. In multivariable-adjusted analyses, HDL-C ≤40 mg/dL and TC/HDL ratio ≥5 were associated with increased risk of IS (hazard ratio [95% confidence interval]: 1.59 [1.23–2.05], p < 0.001 and 1.47 [1.15–1.87], p < 0.001), but not TC or LDL-C. In adjusted analysis, a strong association between TG and IS was diminished. In the MI-free sample (n = 5,875, aged 64 ± 10 years, 58% female; 403 MI events), all lipid markers were associated with MI risk. A genetic risk score comprising 47 known determinants of circulating HDL-C was not associated with IS. CONCLUSIONS: In a middle-aged to elderly community sample, we observed that low HDL-C and high TC/HDL-C ratio, but not LDL-C or TG were associated with risk of incident IS. We observed the usual associations between lipids and risk of MI. Our findings suggest an important, but less likely causal, role of HDL-C over other lipid biomarkers for optimal stroke risk stratification.